A Design of Rheoencephalography Acquisition System Based on Bioimpedance Measurement as the Basis for Assessment of Cerebral Circulation - Lai, Huu Phuong Trung; Vu, Duy Hai; Phan, Dang Hung; Dao, Viet Hung; Dao, Quang Huan; Chu, Quang Dan (Old Journal, 2018)
To evaluate human’s cerebral blood flow (CBF), electrical rheoencephalography (REG) is one of the most notable electrophysiological technique, which has been investigated for a long period. This technique non-invasively measures the electrical impedance of the cranial cavity region through scalp electrodes reflecting the changes in brain’s conductivity due to blood circulation during cardiac cycles. This paper aims to present a design of low-cost system able to continuously record rheoencephalography signal using bioimpedance method. This REG system comprises of main components such as: voltage-controlled current source (VCCS), signal recorder, AM demodulator, analog-to-digital converter, digital signal processor, and signal displayer. This design has a prominent feature that allows to measure the signal without requiring of high resolution ADC (usually 24 bit) and utilizes the simple envelop detecting circuit for AM demodulator. The high-frequency VCCS in the design is also thoroughly designed to ensure the quality of recording signal. The design is implemented, and then is evaluated on simple RC series model for static impedance and standard bio-impedance simulation device (with two kind of waveforms) for dynamic impedance. The results show the high correlation between the standard and recorded signals: R2 is 0.9815 for RC series model; RMSE and rRMSE for waveform 1 are 17.14 and 0.0857%; RMSE and rRMSE for waveform 2 are 13.58 and 0.0679% correspondingly.